Comparison between the levels of anti mullerian hormone after treatment with clomid versus letrozole in polycystic women: an experimental study - Manal Madany Abdel Qader; Shatha Sami Hussein; Huda Fadhil Jadi (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the effect of two ovulation induction drugs on anti-Mullerian hormone level in polycystic women. Method: The experimental cohort study was done at the infertility outpatient clinics of Al-Yarmouk Teaching Hospital, Baghdad, Iraq, from May 2020 to April 2021, and comprised infertile women aged 18-35 years with confirmed diagnosis of polycystic ovarian syndrome. Baseline blood level of anti-Mullerian hormone was tested in all patients. The patients were divided into two groups. Group A patients received clomid 50mg twice daily to a maximum of 200mg for 5 days starting from the third day of the menstrual cycle. Group B patients received letrozole 2.5mg twice daily for 5 days starting from the third day of the menstrual cycle. After ovulation induction on day 12-14, a second sample of serum anti-Mullerian hormone was tested, and intergroup comparisons were done. Data were analysed by using the available statistical package of SPSS-28 (Statistical Packages for Social Sciences- version 28). Students-t-test , Paired-t-test , Pearson correlation , t-test or ANOVA test Statistical significance was considered for P value equal or less than 0.05. Results: Of the 83 women, 41(49.4%) were in Group A with mean age 26.0±4.9 years, while Group B had 42(50.6%) subjects with mean age 27.0±5.1 years. Post-intervention, the level of anti-Mullerian hormone decreased significantly in both groups (p<0.05). The decrease in Group B was more than Group A, but the difference was not significant (p>0.05). Conclusions: Ovulation induction drugs clomid and leterzole decreased the level of anti-Mullerian hormone significantly. Key Words: Polycystic Ovary, Anti-Mullerian Hormone, Letrozole, Infertility, Ovulation Induction, Ambulatory Care, Menstrual Cycle, Clomiphene